Efektifitas Pemakaian Material Akustik pada Gereja Bethel Indonesia (GBI) Musi Palem Indah Palembang - Anta Sastika; Sandra Eka Febrina (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2022)
The use of acoustic materials in the Indonesian Bethel Church Building of Musi Palem Indah Palembang is very much needed considering this building functions as a worship space. The use of a sound system and audio-visual equipment as well as sound coming from the congregation will affect the noise level produced, which is 80 to 85 dB, where the normal threshold is only 30 - 50 dB. Internal noise factor is also influenced by external noise generated from vehicles and activities that take place around the building. The choice of acoustic material used can be effective if it is in accordance with the amount of sound production or the level of noise that arises. The purpose of this study was to determine the effectiveness of the use of acoustic materials used in Bethel Church of Indonesia Musi Palem Indah Palembang through measurement and analysis using descriptive quantitative methods. This study concludes that the acoustic material used at the Bethel Indonesia Musi Palem Indah Palembang Church is less effective in reducing noise levels, especially during the worship process.